2020
DOI: 10.3389/fpsyg.2020.00089
|View full text |Cite
|
Sign up to set email alerts
|

Conservatory Musicians’ Temporal Organization and Self-Regulation Processes in Preparing for a Music Exam

Abstract: Performing at the very highest levels requires rigorous preparation before the important performance. Musicians and especially music students encounter many challenges when preparing themselves for an important musical performance. This study sought to identify and analyze the context-specific temporal organization and self-regulation efforts that music students employ during their preparation period. Conservatory musicians were recruited from an Australian University Conservatorium. Thirteen conservatory musi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
(92 reference statements)
1
7
0
Order By: Relevance
“…Regarding different types of performance preparation, long-term preparation, involving the time allotted and the quality of practice, was shown to have a significant impact on performance. This was consistent with the findings of Antonini Philippe and Güsewell (2016) and Antonini Philippe et al (2020), which suggested that preparation was a crucial aspect in a successful performance. In all fields, but especially in music, the time given to practice is one of the most important factors of success (Sloboda et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding different types of performance preparation, long-term preparation, involving the time allotted and the quality of practice, was shown to have a significant impact on performance. This was consistent with the findings of Antonini Philippe and Güsewell (2016) and Antonini Philippe et al (2020), which suggested that preparation was a crucial aspect in a successful performance. In all fields, but especially in music, the time given to practice is one of the most important factors of success (Sloboda et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…What did you think about it? This type of interview was tested in different studies involving athletes (Antonini Philippe & Güsewell, 2016) and, more recently, musicians (e.g., Antonini Philippe et al, 2018; Antonini Philippe et al, 2020; Antonini Philippe & Güsewell, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several studies in this area have been carried out in the specific contexts of informal learning (Ruismäki, et al, 2012; Seddon & Biasutti, 2009b) and private lessons (Kruse et al, 2013; Pike & Shoemaker 2013), rather in than more formal settings such as conservatories. Online examinations, which require musicians to demonstrate complex abilities (Antonini Philippe et al, 2020), were not tested. These studies often adopted a case study methodology, involving few participants, which limits the generalizability of their results (Kruse et al, 2013; Pike & Shoemaker, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies showed that dealing with music-specific high-pressure challenges is highly individual and diverse, and depends on multiple factors (see, e.g., Buma et al, 2015 ; Oudejans et al, 2017 ). When dealing with the wide range of practice routines at different practice stages (see Antonini Philippe et al, 2020 ) and the very different pedagogical approaches of instrumental and vocal teachers, it is very difficult to assess the impact of conscious changes in attentional focus on musical learning. This is also supported by anecdotic evidence from discussions with many music students in different lectures, where practice and teaching routines, the practice stage, and the musical literature play a major role.…”
Section: Discussionmentioning
confidence: 99%